Letter from JSCDM Team - Triphine Dusabimana (Journal of the Society for Clinical Data Management, 2026)
SCDM’s mission has always been clear: to shape, empower, and equip the clinical data professionals of the future. Within this mission, Vision 2030 charts our path forward, and JSCDM plays a central role, serving as both scientific anchor and catalyst for the knowledge our global community depends on.